2017
DOI: 10.1039/c6fo01529h
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin suppresses the JAK/STAT pathway in a cellular model of intestinal inflammation

Abstract: Current treatment strategies for inflammatory bowel diseases (IBDs) are associated with a lower efficacy and with several side effects that strongly affect the quality of life of IBD patients. Consequently, the development of new therapies, combining efficacy and safety is an important goal in the field of intestinal inflammation. In this context, evidence supports that polyphenols can be promising candidates due to their ability to modulate intracellular inflammatory signalling cascades. Luteolin, a naturally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(54 citation statements)
references
References 69 publications
3
50
0
1
Order By: Relevance
“…The results agree with a previous study in human multiple myeloma cells [23]. Luteolin, a natural flavonoid with potent anti-inflammatory properties, has believed to be able to block the JAK/STAT pathway [56]. After luteolin treatment, IL-6 affected either STAT3 phosphorylation or HO-1 expression was inhibited ( Figure 7B).…”
Section: Discussionsupporting
confidence: 92%
“…The results agree with a previous study in human multiple myeloma cells [23]. Luteolin, a natural flavonoid with potent anti-inflammatory properties, has believed to be able to block the JAK/STAT pathway [56]. After luteolin treatment, IL-6 affected either STAT3 phosphorylation or HO-1 expression was inhibited ( Figure 7B).…”
Section: Discussionsupporting
confidence: 92%
“…It is well documented that the STAT pathway is not only associated with the inflammatory process in IBD; however, is additionally associated with further serious conditions, including colorectal cancer development (38,39). Recent studies demonstrated that luteolin, a naturally occurring flavonoid, inhibited the Janus kinase (JAK)/STAT pathway in cytokine-induced HT-29 cells, a human epithelial cell line (39). Curcumin, a natural phenol, suppressed inflammation of TNBS-induced colitis in mice via STAT signaling (40).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, taxifolin glycoside significantly reduced atopic dermatitis by effects on iNOS and COX-2 [ 35 ] and also ameliorated cerebral ischemia-reperfusion injury by inhibiting NF-κB activity [ 38 ]. However, NLEE contains luteolin which suppressed inflammation in several model through JAK/STAT and/or NF-κB pathway [ 39 40 41 ]. Luteolin reduced iNOS expression through inhibition of NF-κB translocation in LPSstimulated RAW 264.7 cells [ 39 ].…”
Section: Discussionmentioning
confidence: 99%